Adrenoleukodystrophy Newborn Screening in the Netherlands (SCAN Study): The X-Factor - Barendsen, Rinse W.; Dijkstra, Inge M. E.; Visser, Wouter F.; Alders, Mariëlle; Bliek, Jet; Boelen, Anita; Bouva, Marelle J.; van der Crabben, Saskia N.; Elsinghorst, Ellen; van Gorp, Ankie G. M.; Heijboer, Annemieke C.; Jansen, Mandy; et al. (Frontiers in Cell and Developmental Biology, 2020)
X-linked adrenoleukodystrophy (ALD) is a devastating metabolic disorder affecting the adrenal glands, brain and spinal cord. Males with ALD are at high risk for developing adrenal insufficiency or progressive cerebral white matter lesions (cerebral ALD) at an early age. If untreated, cerebral ALD is often fatal. Women with ALD are not at risk for adrenal insufficiency or cerebral ALD. Newborn screening for ALD in males enables prospective monitoring and timely therapeutic intervention, thereby preventing irreparable damage and saving lives. The Dutch Ministry of Health adopted the advice of the Dutch Health Council to add a boys-only screen for ALD to the newborn screening panel. The recommendation made by the Dutch Health Council to only screen boys, without gathering any unsolicited findings, posed a challenge. We were invited to set up a prospective pilot study that became known as the SCAN study (SCreening for ALD in the Netherlands). The objectives of the SCAN study are: 1) designing a boys-only screening algorithm that identifies males with ALD and without unsolicited findings; 2) integrating this algorithm into the structure of the Dutch newborn screening program without harming the current newborn screening; 3) assessing the practical and ethical implications of screening only boys for ALD; 4) setting up a comprehensive follow-up that is both patient- and parent-friendly. We successfully developed and validated a screening algorithm that can be integrated into the Dutch newborn screening program. The core of this algorithm is the “X-counter”. The X-counter determines the number of X chromosomes without assessing the presence of a Y chromosome. The X-counter is integrated as second tier in our 4-tier screening algorithm. Furthermore, we ensured that our screening algorithm does not result in unsolicited findings. Finally, we developed a patient- and parent-friendly, multidisciplinary, centralized follow-up protocol. Our boys-only ALD screening algorithm offers a solution for countries that encounter similar ethical considerations, for ALD as well as for other X-linked diseases. For ALD, this alternative boys-only screening algorithm may result in a more rapid inclusion of ALD in newborn screening programs worldwide.